The Relationship Of Mother’s Knowledge With The Incident Of Stunting In Toddler - Novianti, Novianti; Roza, Siska Desta; Bahri, Serli; Mutmainnah, Sitti (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Short Toddlers (Stunting) is a nutritional status based on the PB/U or TB/U index where in the anthropometric standard for assessing children's nutritional status, the measurement results are at the threshold (Z-Score) <-2 SD to -3 SD ( short/ stunted) and <-3 SD (very short/ severely stunted). Stunting is a problem of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to the provision of food that is not in accordance with nutritional needs. Stunting can occur when the fetus is still in the womb and only appears when the child is two years old. To find out the relationship between maternal knowledge and stunting incidents among toddlers in Alie Liem Village, Blang Mangat District, Lhokseumawe City in 2023. The design of this research is an analytical survey with a cross sectional approach, which means that all variables are observed at the same time as the research takes place and data and information collection is carried out at the same time. There is a significant relationship between maternal knowledge and the incidence of stunting among toddlers in Alue Liem Village, Blang Mangat District, Lhokseumawe City (p = 0.006, OR= 8.325).